Case series: Diquat poisoning with acute kidney failure, myocardial damage, and rhabdomyolysis - Guangcai Yu; Guangcai Yu; Jieru Wang; Jieru Wang; Tianzi Jian; Longke Shi; Longke Shi; Liwen Zhao; Liwen Zhao; Yaqian Li; Yikai Gao; Yikai Gao; et al. (Frontiers Media S.A., 2022)
Diquat is a herbicide that can have deleterious effects on the kidneys, liver, heart, lungs, and central nervous system on ingestion. Diquat poisoning-associated rhabdomyolysis has rarely been reported. We describe two cases of diquat poisoning with acute renal failure, myocardial damage, and rhabdomyolysis. Case 1: A 17-year-old man experienced anuria after ingesting ~200 mL of diquat 16 h prior. On admission, his creatinine (400 μmol/L), urea (11.7 mmol/L), creatine kinase (2,534 IU/L), and myohemoglobin (4,425 ng/mL) concentrations were elevated. Case 2: An 18-year-old woman who ingested ~200 mL of diquat 5.5 h prior to admission had normal creatinine, urea, and creatine kinase concentrations. Eleven hours after ingestion, she developed anuria with elevated creatinine (169 μmol/L) concentration; her creatine kinase (13,617 IU/L) and myohemoglobin (>3,811 ng/mL) concentrations were remarkably elevated 24 h after ingestion. Both patients also had elevated aminotransferase and myocardial enzyme concentrations. After undergoing hemoperfusion and hemofiltration, blood diquat concentrations in cases 1 and 2 on admission (16/6 h after ingestion), after hemoperfusion (20/11 h after ingestion), and after 8 h of hemofiltration/8 h of hemofiltration and 2 h of hemoperfusion (29/21 h after ingestion) were 4.9/9.1, 3.4/5.4, and 1.5/1.2 μg/mL, respectively. Severe diquat poisoning can cause acute kidney failure and rhabdomyolysis. Rhabdomyolysis may induce myocardial injury, aggravating kidney damage, and also increase transaminase concentration. Hemoperfusion and hemofiltration could be effective treatments for eliminating diquat in the blood.